(untitled) (CIPEEX, 2026)
The present study seeks to understand the role of invalidating environments in the development and maintenance of Borderline Personality Disorder (BPD), emphasizing how Dialectical Behavior Therapy (DBT) addresses this phenomenon. BPD is characterized by emotional instability, impulsivity, self-destructive behavior, and difficulties in interpersonal relationships. The literature indicates that invalidating environments, in which children’s emotional experiences are disregarded, punished, or trivialized, significantly contribute to the emotional dysregulation that characterizes the disorder. DBT, created by Marsha Linehan, is presented as a therapeutic approach that balances acceptance and change, providing practical strategies for emotional regulation, distress tolerance, interpersonal effectiveness, and mindfulness. The aim of this research is to investigate, through Grounded Theory, how the concept of the invalidating environment is understood and applied in DBT, and how it impacts clinical practice with borderline patients. It is concluded that the investigation of this concept is relevant for understanding the mechanisms that sustain BPD and for improving clinical practice, preventing the therapeutic setting itself from becoming an invalidating environment.